Validity of Scale and Evaluation of Students’ Attitudes toward Computers. Compare with Students’ Attitudes toward Physical Education and Physical Activity - Antoniou Παναγιώτης; Patsi Χαρίκλεια; Mpempetsos Ευάγγελος; Yfantidou Γεωργία (Inquiries in Physical Education and Sport, 2006)
The purpose of the present study was to examine whether or not the use of new technologies affects students’ participation in physical activities. A number of 252 junior high school students, aged 17± 2, participated in the research. For the examination of the time they spent either in computers or physical activities, a diary was used in which they noted down their activities. All students were given the questionnaires accompanied by the diary, in which they tracked down the time in minutes they spent in the two objectives for 26 days. The results confirmed the reliability and validity of computer attitude scale. The analysis revealed four factors. a) Affective, b) Perceived Usefulness, c) Perceived control, d) Behavioral. No variation was found between boys and girls in attitudes towards computers. Both sexes expressed the opinion that with the computer they organized better their work and that the use of computer didn’t scared them. There was also no variation between boys and girls in attitudes towards PE, perhaps because they begin sports from such an early age that it is possible to adopt a positive attitude towards exercise. Today the participation of both sexes in sports is high, additionally with older ages that society didn’t allow the participation of women in sports, and it is probably their opinions not to be different. Finally, students preferred surfing the Net and playing computer games than participating in sports.